AKHLAK VALUES INTERNALIZATION THROUGH THEMATIC LEARNING IN PRIMARY SCHOOL OF NATURAL BOGOR - Kulsum, Robi’ah Ummi (Tawazun: Jurnal Pendidikan Islam, 2018)
Starting from the doubt of the elementary school teachersto implement thethematic learning, the writer was chalanged to see the other sideof thethematic learning, with respect to the cultivation moral values as the manifestation of the effective domain. The main objective of this study is to findpatterns ofinternalization of moral values through thematic learning in SDA Band to formulate the concept ofinternalization of moral values through thematic learning. The studywas conducted usingqualitative descriptive by case study approach. Data collection was done through deep interviews technique, field observations, and documentation study. From this study, the writer found that: 1st)the concept of akhlak values internalization in SDAB is done with an institution values-based called by SALAM that is based on the teachings of akhlak in Islam; 2nd) in the implementation, the achievement of the institution values “SALAM” is very useful in to the achievement of the SDAB ultimate goal of education using a thematic approach. The use of other methods to support the process of akhlak values internalization, such as by imitation, habituation, motivation and enforcement was done beyond through teaching method; 3rd) The concept of internalization of moral values through thematic learning is a learning condition stated particular moral values where thematic based approach with class, school cultur and community design, also various kind of methods applied sistematically used. Keywords : AkhlakValues, Thematic Learning.